1969
DOI: 10.1099/0022-1317-5-4-493
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Mycobacteriophage on Cell-wall Components

Abstract: SUMMARYHeat-killed whole cells, purified cell walls, and the three main polymers isolated from cell walls of Mycobacterium sp. ATCC 607, M. smegmatis AliCe 14468 and M. phlei ATCC 11758, were examined to find the receptor sites for phage GS-7. Among heat-killed whole cells of insusceptible species, M. srnegmatis adsorbed the phage at a higher rate than the susceptible Mycobacterium sp. ATCC 607, whereas M. phlei did not adsorb the phage at all suggesting a distinction between phage-resistance (absence of recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In t h~s connection, it is interesting to mention that the 'rhodochrous' complex has both the ~a r e n t a l and back niutant strains exclusively show the adsorption of mycobacteriophages. In the study of mycobacteriophage receptors, mycolic acid was shown to be an essential component of the receptor substance of mycobacteriophage GS7 (25). Similarly, adsorption of nocardiophage M N P l onto OR-variants may be attributed to the surface coniponent(s) common to those of Nocardiu, presumably nocardomycolates produced in the OR-variants, although the receptor substances for nocardiophages have not been confirmed at present.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In t h~s connection, it is interesting to mention that the 'rhodochrous' complex has both the ~a r e n t a l and back niutant strains exclusively show the adsorption of mycobacteriophages. In the study of mycobacteriophage receptors, mycolic acid was shown to be an essential component of the receptor substance of mycobacteriophage GS7 (25). Similarly, adsorption of nocardiophage M N P l onto OR-variants may be attributed to the surface coniponent(s) common to those of Nocardiu, presumably nocardomycolates produced in the OR-variants, although the receptor substances for nocardiophages have not been confirmed at present.…”
Section: Discussionmentioning
confidence: 94%
“…The following conlpounds were applied to discs: (25,50, and I00 pg). All plates were i n c~~b a t e d in darkness for 18 h, followed by carefully overlaying 5 x 1 0 8 C F U of strain N715 in soft agar to form a lawn.…”
Section: Ger~etic At~alyses I Atte~~ipts To Detect Bncter'iophngcmentioning
confidence: 99%
“…22 for reasons] in bacteria grown in Dubos liquid medium, resuspended in heart in fusion broth (Difco) enriched with 0.04 M CaCl2 and 0.5°/o glycerol (HIBG) and exposed for 60 min to INH, PTH, DDS or their combinations. Then the phage was added and samples were taken after 30 and 60 min and placed immediately into crushed ice to chill and centrifuged at 3,000 rpm to sediment adsorbed phage [18]. Unadsorbed phage was assayed by plating appropriate dilutions on the N-l agar medium [37] (Difco agar base was substituted by Difco agar and trypticase, BBL, 1.5%> and 15 g, respectively) using the rou tine test dilution (RTD) method.…”
Section: Methodsmentioning
confidence: 99%
“…According to a number of reports regarding the phage receptor sites of bacteria, sugar components seem to play an important role as determinant groups of phage receptors in many species of gram-negative bacteria [2, 3, 9,16]. The phage receptor sites in grampositive bacteria, on the other hand, are composed of various components such as teichoic acid [5,8,17,19], lipopolysaccharide [10], mucopeptide [13] and L-rhamnose [18] . It is known that considerable amounts of glutamic acid, alanine, glucosamine, galactose and 2, 6-diaminopimelic acid are contained in the cell walls of Bacillus anthracis [14,15].…”
mentioning
confidence: 99%